Microplastics-Induced Eryptosis and Poikilocytosis in Early-Juvenile Nile Tilapia (Oreochromis niloticus) - Hamed, Mohamed; Osman, Alaa G. M.; Badrey, Ahmed E. A.; Soliman, Hamdy A. M.; Sayed, Alaa El-Din H. (Frontiers in Physiology, 2021)
The present study was aimed to examine the effectsof microplastics on erythrocytes using eryptosis (apoptosis) andan erythron profile (poikilocytosis and nuclear abnormalities)as novel biomarkers in Nile tilapia.Four groups of fishes were used; the first group was the control group, the second group was exposed to (1mg/L of MPs), the third group was exposed to (10mg/L of MPs), and the fourth group was exposed to (100mg/L of MPs) for 15 days and 15 days of recovery. The fish treated with microplasticsexperienced a significant rise in the percentage of eryptosis, poikilocytosis and nuclear abnormalities of red blood cells(RBCs) compared with the control group in a concentration-dependent manner. Poikilocytosis of microplastics exposed- groups included sickle cell, schistocyte,elliptocyte,acanthocyte, and other shapes.Nuclear abnormalities of microplastics exposed- groups included micronuclei,binucleated erythrocytes, notched, lobed, blebbed, and hemolyzed nuclei. After the recovery period, a greaterpercentage of eryptosis, poikilocytotic cells and nuclear abnormalities in RBCs werestillevident in microplastics-exposed groups compared with the control group.The results reinforceconcerns regarding the toxicity ofmicroplastics in tilapia.